Peran Seni Dalam Mempertahankan Identitas Budaya Lokal Di Era Modern - Saputra, Rifki; Hasanah , Niswatun; Kamaludin; Azis, Muhammad; Putra, Muh Ardiansyah; Armayadi, Yoga (Besaung : Jurnal Seni Desain dan Budaya, 2024)
This study is a systematic literature review utilizing sources from Scopus, DOAJ, and Google Scholar, focusing on publications from 2013 to 2023. The findings assert the significant and relevant role of cultural arts in preserving local identities in the modern era. Cultural arts serve as social cohesion agents, safeguarding local traditions and values amidst the changes and influences of globalization and modernization. Various forms of artistic expression such as painting, music, dance, and literature play a crucial role in strengthening and preserving local identities, fostering awareness of cultural diversity within the dynamics of the modern world. Cultural arts also facilitate dialogue between local traditions and modern innovations, enabling productive interaction between existing and emerging elements, and stimulating critical reflection on the interpretation of traditional values in the evolving context of time. However, there are gaps in this research highlighting the lack of in-depth studies on the impact of modern technology on cultural artistic expression and local identity, which require further attention in the future.